4x+26=7x+2

Simple and best practice solution for 4x+26=7x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+26=7x+2 equation:



4x+26=7x+2
We move all terms to the left:
4x+26-(7x+2)=0
We get rid of parentheses
4x-7x-2+26=0
We add all the numbers together, and all the variables
-3x+24=0
We move all terms containing x to the left, all other terms to the right
-3x=-24
x=-24/-3
x=+8

See similar equations:

| 9x÷6=29 | | 21-5x=4x-5 | | (2x-4)^2=64 | | 3/(2x-1)+4/(2x+1)=7/2x | | 2x2-17x+36=0 | | 5b-2=-7 | | (0.5z+4)/(1.2z+6)=5/3 | | 3y2-14y-5=0 | | 3x2+16x+20=0 | | (2-9x)/(16+5x)=0 | | ((2-9x)/(16+5x))=0 | | 3=y-44/10 | | 1|3(9-2x)=x+1 | | -15+3x=8x | | ((2-9z)/(17-4z))=4/5 | | -16+3x+1=8x | | 12/x-1=2/3 | | 12/c-1=2/3 | | ((4x+1)/3)+((2x-1)/2)-((3x-7)/5)=6 | | -4y-8=-8 | | 8=64/y | | 3z-12=-6 | | ((z+5)/6)-((z-1)/9)=(z+3)/4 | | d/4-8=-2 | | (z+5)/6-(z-1)/9=(z+3)/4 | | 10=x*18 | | 7+30x0.5=18.5 | | 3x=20÷7-x | | s(-3)=14-2(-3) | | 2c^2+2c-1=0 | | 1*5+2/1-2=x | | q(1+1/2)=9 |

Equations solver categories